Exploring the Role of Sustainable Intellectual Capital in Enhancing Sustainable Performance: A Case Study - Mulyana, Aam Rachmat (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2026)
Intellectual Capital (IC) is increasingly recognized as a critical asset for organizational success. In parallel with rising awareness of sustainability, the concept of Sustainable Intellectual Capital (SIC) has emerged. Despite its relevance, empirical research on SIC is still scarce, especially regarding its linkage to sustainable organizational performance. This study addresses this gap through a case study of an MSME supported by PT LEN, this study aims to assess how internal organizational stakeholders perceive the concepts of SIC, sustainability, and sustainable performance, as well as to gain a deeper understanding of the impact of SIC on the economic, social, and environmental dimensions of sustainable organizational performance. The evidence indicates that stakeholders are not familiar with the concept of SIC and tend to overemphasize the environmental dimension when referring to sustainability and sustainable performance. Furthermore, the findings reveal that the organization’s sustainable performance is influenced by all components of SIC—human, structural, and relational capital. This study contributes to the development of two distinct yet complementary streams of research: intellectual capital and sustainability capabilities. It also offers important managerial implications for industrial organizations concerned with their performance. Finally, any generalization to other contexts should be made on a purely theoretical basis.